2014
DOI: 10.1631/jzus.b1300220
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies

Abstract: Abstract:The association between the estrogen receptor α gene (ESR1) PvuII polymorphism (c.454-397T>C) and coronary artery disease (CAD) is controversial. Thus, we conducted a meta-analysis to evaluate the relationship. Data were collected from 21 studies encompassing 9926 CAD patients and 16 710 controls. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the relationship between PvuII polymorphism and CAD. The polymorphism in control populations in all studies followed Hardy-Weinberg e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
1
18
0
5
Order By: Relevance
“…Mechanisms by which coexistence of CAD and ARAS is associated with HFpEF are under investigation (Groban and Kitzman, 2010;Wang and Shi, 2014). The progressive increase in cardiac diastolic dysfunction leading to a worsening of CAD and ARAS is partly explained by factors such as increased afterload, renal hypertension resulting from ARAS, myocardial ischemia, overactivation of RAAS, and inflammation (Ding et al, 2014). Risks that increase with coexisting CAD and ARAS complicated by HFpEF include oxidative stress, de-arrangements in calcium-phosphate homeostasis, and conditions promoting coagulation, all of which share similar pathogenic factors associated with accelerated atherosclerosis and endothelial dysfunction (de Silva et al, 2005;Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which coexistence of CAD and ARAS is associated with HFpEF are under investigation (Groban and Kitzman, 2010;Wang and Shi, 2014). The progressive increase in cardiac diastolic dysfunction leading to a worsening of CAD and ARAS is partly explained by factors such as increased afterload, renal hypertension resulting from ARAS, myocardial ischemia, overactivation of RAAS, and inflammation (Ding et al, 2014). Risks that increase with coexisting CAD and ARAS complicated by HFpEF include oxidative stress, de-arrangements in calcium-phosphate homeostasis, and conditions promoting coagulation, all of which share similar pathogenic factors associated with accelerated atherosclerosis and endothelial dysfunction (de Silva et al, 2005;Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen receptors are present in the hypothalamus, olfactory lobe, amygdala, hippocampus, cerebral cortex, cerebellum, pituitary gland, bone tissue (osteoblasts and osteoclasts), the cardiovascular system, and the liver. A high ERa expression was observed in: endometrial glandular epithelium, mammary glands, pituitary gland, adrenal glands, endothelium, and vascular smooth muscle (ERa plays a more important role in cardioprotection than ERb, considering the participation in vasodilatation, neovascularisation, and weakening cell apoptosis in the cardiac muscle [7]), as well as the liver and testis.…”
Section: Oestrogen Receptors -Division and Role In The Female Bodymentioning
confidence: 99%
“…In many studies, a relationship was confirmed between PvuII polymorphism carrier state and many abnormalities [7], such as: breast cancer [10], atherogenic lipid profile changes, hypertension, and coronary atherosclerosis [25]. A controversial issue in many studies is the relationship between PvuII polymorphism and the risk of development of ischaemic heart disease (IHD) [7].…”
Section: Consequences Of Oestrogen Deficiency and Oestrogen Receptor mentioning
confidence: 99%
See 2 more Smart Citations